Agathis moorei (Lindley) Masters. Agathis ovata (Moore) Warburg - Sarrailh, Jean-Michel; Chauvin, Jean-Paul; Litaudon, Marc; Dumontet, Vincent; Pieters, Romuald (BOIS & FORETS DES TROPIQUES, 2003)
Le résumé est disponible dans le fichier PDF de l'article.